2014
DOI: 10.1371/journal.pone.0084836
|View full text |Cite
|
Sign up to set email alerts
|

Antiadhesive Properties of Abelmoschus esculentus (Okra) Immature Fruit Extract against Helicobacter pylori Adhesion

Abstract: BackgroundTraditional Asian and African medicine use immature okra fruits (Abelmoschus esculentus) as mucilaginous food to combat gastritis. Its effectiveness is due to polysaccharides that inhibit the adhesion of Helicobacter pylori to stomach tissue. The present study investigates the antiadhesive effect in mechanistic detail.MethodologyA standardized aqueous fresh extract (Okra FE) from immature okra fruits was used for a quantitative in vitro adhesion assay with FITC-labled H. pylori J99, 2 clinical isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
65
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 35 publications
6
65
0
2
Order By: Relevance
“…Okra's polysaccharides were particularly effective at inhibiting the adhesion of Helicobacter pylori, a bacterium that dwells in the stomach and can cause gastritis and gastric ulcers if left unchecked. Therefore, eating more okra can keep our stomach clean and create an environment that prevents destructive cultures from flourishing (Messing et al, 2014). Okra is used to supports colon health.…”
Section: Health Benefits Of Okramentioning
confidence: 99%
See 1 more Smart Citation
“…Okra's polysaccharides were particularly effective at inhibiting the adhesion of Helicobacter pylori, a bacterium that dwells in the stomach and can cause gastritis and gastric ulcers if left unchecked. Therefore, eating more okra can keep our stomach clean and create an environment that prevents destructive cultures from flourishing (Messing et al, 2014). Okra is used to supports colon health.…”
Section: Health Benefits Of Okramentioning
confidence: 99%
“…Okra is better ingested when joined along with other healthy veggies. Consuming okra has truly numerous advantages, simply bear in mind to eat natural veggies as opposed to processed veggies (Messing et al, 2014). Okra is used to controls the body's cholesterol level.…”
Section: Health Benefits Of Okramentioning
confidence: 99%
“…"Okra"'s polysaccharides were particularly effective at inhibiting the adhesion of Helicobacter pylori, a bacterium that dwells in the stomach and can cause gastritis and gastric ulcers if left unchecked. Therefore, eating more "Okra" can keep our stomach clean and create an environment that prevents destructive cultures from flourishing [77]. "Okra" is used to supports colon health.…”
Section: Health Benefits Of "Okra"mentioning
confidence: 99%
“…"Okra" is better ingested when joined along with other healthy veggies. Consuming "Okra" has truly numerous advantages, simply bear in mind to eat natural veggies as opposed to processed veggies [77].…”
Section: Health Benefits Of "Okra"mentioning
confidence: 99%
“…This plant has been used to treat various disorders, amongst which inflammatory conditions [13,14]. Some recent studies have demonstrated antinociceptive and anti-inflammatory activity of the A. esculentus lectin (AEL) [15].…”
Section: Introductionmentioning
confidence: 99%